The Portrayal of Women in Selected Billboard’s Top 100 Chart Songs (2015-2018): A Semiotic Analysis - Nurul Laela Kusumadewi; Dadang Sudana; Ernie Diyahkusumaning Ayu Imperiani (Universitas Pendidikan Indonesia (UPI), 2020)
Music and song are vehicles of meanings, hence, depictions of women can be presented through them. This study investigates women’s portrayal in selected Billboard’s Year-End Chart songs through its significations which includes denotation, connotation, and myth constructed in the lyrics. Three major theoretical frameworks were used in this present study. The first theory is two orders of signification from Roland Barthes (1957) which was used to analyze the selected songs. The second theory is the bases of social power from French Raven (1959). The third theory is resilience model from Benard (2004). The findings reveal that in connotation level women are portrayed as powerful and resilient. The findings indicate that as a powerful being, women possess certain types of powers. Meanwhile as a resilient being, women possess particular qualities of resilience. From gender stereotype perspective, the myth implies that women possess dominating agency dimension alongside communion and competence dimensions, which implies that stereotype on women is not likely to be rigid.Keywords: Barthes’ two orders of signification, portrayal, powerful, resilient, women.